(untitled) (Revista Contexto & Saúde, 2020)
This study aims to describe the nutritional therapy and the caloric-protein adequacy of critically ill patients who developed acute kidney injury (AKI). It is an observational, prospective cohort study carried out with patients on enteral therapy, admitted to a public ICU. The caloric-protein inadequacy was considered to be patients who did not reach 80% of the total energy value within 07 days of hospitalization and protein supply <1.5 g / kg of weight / day. Differences between groups were obtained using the t-Student test and Pearson’s chi-square test. Inadequate energy and protein, on the 7th day, was observed in male patients, aged less than 50 years (61.1%), with comorbidities (66.7%), the mean weight was 85.78 ± 13.91 kg, receiving protein <1.5 grams (80.8%), manifested acute kidney injury (55.6%), remained hospitalized for 15.72 ± 10.80 days and died (83.3% ). Among patients with inadequate protein, both on the 3rd and 7th day, they were high among patients who died (p<0.05). In the occurrence of AKI, there was a greater inadequacy in the energy value (28.6%), as well as a higher incidence of complications for the non-infusion of the diet until the 3rd day (52.3%) when compared with those without AKI (p <0,05).